Gestão de recursos hídricos no estado do Amazonas: uma análise comparativa - Ferreira, Anita Rocha Alves dos Santos (2008)
The present study analyzes the legal mechanisms and the management system for water resources at the Amazonas state and its relationship with the Law 9.443, from January 8th, 1997, emphasizing the different variables that exist in the great hydrographic basin of Amazonas, which are fundamental for the conception of the legal mark in the state of Amazonas. It was also considered that isolation and distance specificity in comparison with other states can not serve as a parameter for using already elaborated models. This work presents the national policy of water resources and describes the current phase of water resources management in the states of Amazonas and Rio de Janeiro. In the following, it develops a criticai analysis of the state law that established the state policy of water resources for Amazonas state, and does a comparative evaluation of the entities and mechanisms from both states. The work methods include a documental and bibliographic research aiming to describe and provide material for a deeper study on the water resource management in the Amazonas state. Field research has been developed in order to obtain a more profound criticai analysis. As a result, it may be emphasized the need for altering current laws and for an administrative restructuring of environmental organs.